Investigation into porous concrete formation peculiarities with a mixed binder composition - Laukaitis, A. (Journal of Civil Engineering and Management, 1995)
Porous concrete is a cheap material produced from local raw materials. That is why, it is important to improve it’s properties, especially the product’s density. This paper deals with porous concrete made using a mixed binder composition (lime+Portlandcement) formation peculiarities and determination of optimal product formation parameters for 300–350 kg/m3 product dependency on the binder mixture composition. A wide density interval (200–500 kg/m3) was investigated to determine the optimal above mentioned porous concrete density parameters. It was determined, that the porous concrete density with a mixed binder composition has a complex dependency from water and dry solids ratio (V/K), mixed binder composition and amount of Al powder. Mathematical equations of porous concrete density on technological parameter were derrived. It was found that the lime contant increase in the lime- Portlandcement binder mixture, lowers Al powder effectiveness, increases the product’s density and decreases the technological operation time duration. Article in Lithuanian. Dujų betono su mišria rišančiąja medžiaga formavimo ypatumų tyrimai First Published Online: 26 Jul 2012